Optimal Correction of Adult Spinal Deformities Requires Restoration of Distal Lumbar Lordosis. (7th May 2021) - Pesenti, S.; Prost, S.; McCausland, A. Muñoz; Farah, K.; Tropiano, P.; Fuentes, S.; Blondel, B.
Abstract : Purpose . The aim of this study is to analyze results according to postoperative pelvic incidence-lumbar lordosis (PI-LL) mismatch in the management of adult spine deformity (ASD) patients. Recently, it has been reported that in addition to lumbar lordosis amount, lordosis repartition between its proximal and distal parts was crucial. Methods . We enrolled 77 consecutive ASD patients who underwent posterior spinal fusion and deformity correction between 2015 and 2018. On preoperative and 1-year follow-up radiographs, we analyzed different parameters such as L1-S1 lumbar lordosis, L1-L4 proximal lordosis (PLL), L4-S1 distal lordosis (DLL), pelvic tilt (PT), sagittal vertical axis (SVA), and PI-LL mismatch. Comparisons were performed according to postoperative PI-LL mismatch (defined as "aligned" when PI-LL was <10°). The relationship between lordosis distribution and postoperative alignment status was investigated. Results . On the whole series, average lumbar lordosis, SVA, and PI-LL improved (28.2° vs.43.5°, 82 vs. 51 mm, and 26°vs. 14°, all p < 0.001, respectively). On the other hand, PT remained unchanged (30° vs. 28°, p > 0.05 ). 35 patients were classified as "aligned" and 42 as "not aligned." Patients from the "aligned" group had a significantly lower PI than patients from the "not aligned" group (52° vs. 61°, p = 0.009 ). Postoperative PLL was not different between groups (18° vs. 16° p > 0.05 ), whereas DLL was significantly higher in the "aligned" group (31° vs. 22°, p = 0.003 ). PI-LL was significantly correlated to DLL (rho = 0.407, p < 0.001 ) but not with PLL (rho = 0.110, p = 0.342 ). Conclusions . Our results revealed that in ASD patients, postoperative malalignment was associated with a lack of DLL restoration. "Not aligned" patients had also a significantly higher pelvic incidence. Specific attention must be paid to restore optimal distal lumbar lordosis in order to set the amount and the distribution of optimal postoperative lumbar lordosis.